2011
DOI: 10.1103/physrevlett.107.195504
|View full text |Cite
|
Sign up to set email alerts
|

Structural Relationship between Negative Thermal Expansion and Quartic Anharmonicity of CubicScF3

Abstract: Cubic scandium trifluoride (ScF 3 ) has a large negative thermal expansion over a wide range of temperatures. Inelastic neutron scattering experiments were performed to study the temperature dependence of the lattice dynamics of ScF 3 from 7 to 750 K. The measured phonon densities of states show a large anharmonic contribution with a thermal stiffening of modes around 25 meV. Phonon calculations with first-principles methods identified the individual modes in the densities of states, and frozen phonon calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
184
2
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 218 publications
(208 citation statements)
references
References 27 publications
21
184
2
1
Order By: Relevance
“…The unique NTE mechanism of SrAu 3 Ge may also be a great playground for further theoretical studies. 15 ■ ASSOCIATED CONTENT…”
Section: ■ Conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…The unique NTE mechanism of SrAu 3 Ge may also be a great playground for further theoretical studies. 15 ■ ASSOCIATED CONTENT…”
Section: ■ Conclusionmentioning
confidence: 99%
“…The simple structure of SrAu 3 Ge, with only four independent atoms in a unit cell, also may be a great playground for further study of NTE in theory. 15 ■ EXPERIMENTAL SECTION Synthesis. All manipulations were performed in a N 2 -filled glovebox (H 2 O < 0.1 ppmv).…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The phonon properties of ScF 3 have been studied using a combination of inelastic neutron scattering experiment with ab initio calculations of lattice dynamics [7]. It was shown that a description of NTE within the quasi-harmonic approximation is not reliable in the case of ScF 3 .…”
Section: Introductionmentioning
confidence: 99%
“…[4]. Two chargetransfer-type satellites, the first one at about 13 eV below the main peaks in the valence-band and the second one with an energy separation of about 9-10 eV, were observed and indicate the strong hybridization effect between Sc 3d and F 2p states [4].The phonon properties of ScF 3 have been studied using a combination of inelastic neutron scattering experiment with ab initio calculations of lattice dynamics [7]. It was shown that a description of NTE within the quasi-harmonic approximation is not reliable in the case of ScF 3 .…”
mentioning
confidence: 99%